2006
DOI: 10.1021/bm0607269
|View full text |Cite
|
Sign up to set email alerts
|

Michael-Type Addition Reactions for the In Situ Formation of Poly(vinyl alcohol)-Based Hydrogels

Abstract: Michael-type addition reactions offer the possibility to obtain in situ formation of polymeric hydrogels in the absence of a radical mechanism for the networking process. We explored such a synthetic route for obtaining a poly(vinyl alcohol) (PVA)-based hydrogel as a potential biomaterial for applications in vitro-retinal replacement surgery. The presence of radicals in the reaction medium can represent a risk for in situ surgical treatment. To circumvent this problem we have applied nucleophilic addition to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…These peaks were not present in the spectrum of the starting material ( Figure 1C) There are two possible reaction routes for chemical modifications of polymers through the use of the glycidyl methacrylate: transesterification and epoxide ringopening mechanisms. 28,29 The reaction mechanism of glycidyl methacrylate and dextran by using DMSO as a solvent has been found that transesterification is the predominant route for the polymer methacrylation. 30 In the case of laminarin, a definitive conclusion cannot be drawn from the NMR and FTIR analysis.…”
Section: Synthesis and Characterization Of Methacrylated Laminarinmentioning
confidence: 99%
“…These peaks were not present in the spectrum of the starting material ( Figure 1C) There are two possible reaction routes for chemical modifications of polymers through the use of the glycidyl methacrylate: transesterification and epoxide ringopening mechanisms. 28,29 The reaction mechanism of glycidyl methacrylate and dextran by using DMSO as a solvent has been found that transesterification is the predominant route for the polymer methacrylation. 30 In the case of laminarin, a definitive conclusion cannot be drawn from the NMR and FTIR analysis.…”
Section: Synthesis and Characterization Of Methacrylated Laminarinmentioning
confidence: 99%
“…[52] Both amines and thiols on proteins participate in the reaction and it is possible to control where the reaction takes place based on the reaction pH relative to the pK a of the amino acid functional group. [2,49] In this study, we go beyond the characterization of secondary structure using Raman spectroscopy to show that quantitative chemical results can be achieved. First, using single amino acids and then full proteins, we compare the extent of reaction and specific reaction site of functionalized amine and thiol groups measured with Raman spectroscopy against standard protocols.…”
Section: Introductionmentioning
confidence: 99%
“…The Michael addition of nucleophiles (amine or thiol group) to α,β-unsaturated carbonyl compounds or α,β-unsaturated sulfones in water forms hydrogels. Various functionalized polymers, such as poly(ethylene glycol) (PEG) [24][25][26], poly(vinyl alcohol) (PVA) [27], N-isopropylacrylamide (NIPAAm) [28], and natural polymers [14,29] have been crosslinked via Michael addition and formed hydrogels. The copper [Cu(I)] catalyzed azide-alkyne cycloaddition is one of the most popular click chemistry reactions.…”
Section: Chemical Hydrogelsmentioning
confidence: 99%